STUDI IN VITRO INHIBISI PROTEIN EGFR PADA SPERMATOGENESIS PERSINYALAN TESTOSTERON NONKLASIK DARI NANOPARTIKEL KITOSAN MENGANDUNG PHYLLANTHUS NIRURI SERTA KAJIAN PUSTAKA SISTEM PENGHANTARAN BERTARGET BADAN GOLGI DAN APLIKASINYA - Ayu Wulandari, Sefta
Phyllanthus niruri is a herb that has various pharmacological activities. In addition to studies related to P. niruri pharmacological activity, there has been one study examined the toxicity of P. niruri from the administration of chitosan nanoparticles containing P. niruri (NP PN) about the inhibition of EGFR (epidermal growth factor receptor) phosphorylation. In this study, further studies were carried out regarding the formulation of chitosan nanoparticles, NP PN with their characterization and inhibition of EGFR protein phosphorylation study in Sertoli cells (TM4) by administering chitosan nanoparticles, P. niruri extract, and NP PN through Western Blot testing. According to the findings, the results of the size characterization, polydispersity index, and zeta potential of chitosan nanoparticles were 151.6 nm; 0.296; and 30 mV while for NP PN it is 170,3 nm; 0.192; and 30.1 mV with entrapment efficiency of 80.1%. The results of the phosphorylation inhibition study on EGFR protein showed that there was no inhibition from the administration of chitosan nanoparticles but inhibition occurred from the administration of P. niruri extract 500 and 2000 ppm also NP PN 125 and 500 ppm (p<0.05). The inhibition of phosphorylation in EGFR protein allows the disruption of the spermatogenesis process because the attachment of germ cells to Sertoli cells is disrupted and affects sperm release. Keywords: testosterone nonclassical pathway, P. niruri, Sertoli cells, phosphorylation, spermatogenesis, nanoparticle, EGFR The Golgi apparatus has the function to sort, modify, deliver and secrete proteins appropriately and can be used as target organelles in drug delivery systems. The presence of fragmentation or structural damage in the Golgi apparatus can change its normal function and it can be used to reduce the expression of proteins in some diseases such as cancer. This literature review aims to review the Golgi apparatus targeted delivery system. The literature search was carried out using the Google Scholar and Pubmed and then selected based on the inclusion and exclusion criteria that have been set. According to the findings in the delivery system to the Golgi apparatus, there is a role of chondroitin sulfate, PLGA-PEG, thiophosphopeptide, L-cysteine , and BSA which can be used as ligands in delivery to the Golgi apparatus. Targeting the Golgi apparatus depends on the presence of sulfhydryl groups and the acidic pH of the Golgi apparatus in cancer cells. There is a role of the enzymes GalNAc transferase and alkaline phosphatase in mediating the delivery of material to the Golgi apparatus and the use of retinoic acid and brefeldin A as Golgi apparatus disrupting compounds that can damage the structure of the Golgi apparatus which are used to suppress cell proliferation and the overexpression of certain proteins in test cells.